Alignment and Misalignment in Personal and Organizational Spiritual Identities. Issue 3 (2nd July 2016) - Crossman, Joanna
ABSTRACT: This article reports on an Australian empirical study that aimed to explore how managers and professionals experience spirituality in the workplace. The rationale for the study lay in the paucity of empirical studies on workplace spirituality in Australia, as compared with the burgeoning literature published in the United States (Bell, Rajendran, & Theiler, 2012, p. 68). Through an inductive and interpretive approach, the analysis gave rise to a grounded theory concerned with personal and organizational spiritual identity. Organizational spiritual identity was communicated through values, practices, discourse, nonverbal artifacts, written documents, policies, and contributions to charities, for example. When personal and organizational spiritual identities were misaligned, the potential for conflict and dilemmas with damaging consequences for employees and organizations intensified.